Reflective Tool for Sustainability Thinking – Craft, Design and Technology Student Teachers’ Narratives - Korkeaniemi, Arttu; Koskela, Teija (Daugavpils University, 2026)
Teacher education is key for education in sustainability and sustainable development. In the Finnish education system, the subject of Craft, Design, and Technology (CDT) is considered an effective platform for teaching sustainability. The view of sustainability, from environmental, economic, and socio-cultural dimensions, has shifted to a more holistic perspective in which all dimensions are regarded as intertwined. This study combines theoretical aspects of sustainability and its inclusion in the subject of CDT. The aim is to investigate CDT student teachers’ meanings of sustainable development in their individual lives and their CDT teaching. The narratives of student teachers (N=47) in survey responses were analyzed to gain insight into their meanings. The analysis resulted in four descriptive subcategories, each reflecting different meanings shaping CDT student teachers’ sustainability thinking. In conclusion, a reflective tool for sustainability thinking in teacher education was created within this study.